Innovation of Customer Chemicals Packaging in Concern of Sustainability - Branská, Lenka; Paták, Michal; Pecinová, Zuzana (Univerzita Hradec Králové, 2020)
Increasing the environmental orientation of manufactured products and business activities is becoming the current trend in the area of corporate management. Logistics activities and the packaging of products are also becoming focal points as they have significant potential to reduce the environmental burden. Great attention is paid to primary packaging, especially if the company uses plastic packaging. The article deals with the possibilities of primary packaging innovation for selected consumer chemical products in order to reduce the volume of used plastics. Possibilities of innovation were identified by content analysis of information obtained in primary qualitative research in a medium-sized company engaged in the production of consumer chemical products. It has been found that the reduction of plastic packaging waste for a selected product can be achieved by replacing the plastic with another material, changing the colour of the plastic packaging, using recycled plastics in packaging production, changing the packaging production technology, through innovations of the packaged product, changes in the management of the sales process, introduction of a plastic packaging reuse system and application of recycling. However, the implementation of individual innovations always means an increase in operating costs, some of which will also require investment costs.
Inovace balení výrobků spotřební chemie v zájmu udržitelnosti
Keywords: supply chain management; packaging; chemical products; dodavatelský řetězec; obaly; čisticí prostředky; úklidové prostředky